Er:YAG laser cleaning of a marble Roman urn. Issue 1 (2nd January 2020) - Andreotti, Alessia; Colombini, Maria Perla; De Cruz, Adele
Abstract: There are very few documented instances of the use of an Er:YAG laser in the cleaning of stone artefacts; however, the cases reported in the literature have shown its effectiveness in the removal of surface organic patinas and lichens. A Roman marble funerary urn (67–100 AD) of archaeological importance was covered with an intractable surface layer that obscured its delicate decorative carving. Chromatographic mass spectrometric and Raman spectroscopic techniques allowed the characterisation of those inorganic and organic materials that had undergone photo-oxidation and biological changes, resulting in the thick encrustation. An Er:YAG laser at 2940nm, with a pulse length of 300µsec, was used for cleaning the urn. Preliminary tests were performed with fluences ranging from 0.7 to 6.4J/cm 2 and in the presence of a variety of wetting agents. The laser cleaning resulted in a sufficiently clean marble surface with the thick deposit of unwanted material removed. Finally, the sensitivity of the method allowed for a compact layer of calcium oxalate to be retained on the marble's surface to help protect it.